Silent Adrenal Pheochromocytoma Coexistent with Corticomedullary Hyperplasia: A Case Incidentally Discovered - Luigi Petramala (European Journal of Case Reports in Internal Medicine, 2017)
Introduction: Pheochromocytoma (PHEO) is a rare catecholamine-producing tumour arising from chromaffin cells in the sympatho-adrenal system, and can present as asymptomatic adrenal incidentaloma (AI). Patient: We describe the case of a 61-year-old woman with a right adrenal mass incidentally discovered, who was biochemically characterized with subclinical hypercortisolism (SH). The patient was scheduled for adrenalectomy because of increasing seizure of the right adrenal gland with a haemorrhagic and focal pseudocystic appearance macroscopically, incidental histological and immunohistochemical PHEO, and micronodular cortico-adrenal hyperplasia. Discussion: This report describes a rare case of incidental non-functioning PHEO coexisting with corticomedullary hyperplasia and SH.